[1]
Introduce young ones to the concept of counting from one to ten while celebrating themes of friendship and community
Keywords: Counting; African American children; Friendship; Communities; Calcul - Romans; nouvelles; etc. pour la jeunesse; Enfants noirs américains - Romans; nouvelles; etc. pour la jeunesse; Amitié - Romans; nouvelles; etc. pour la jeunesse; Communauté - Romans; nouvelles; etc. pour la jeunesse; picture books; board books; Board books; Children's stories - Pictorial works; Picture books; Livres d'images; Livres tout carton